2020
DOI: 10.1111/apt.15824
|View full text |Cite
|
Sign up to set email alerts
|

Letter: faecal microbiota transplantation for IBS

Abstract: We read with interest the recent paper by Lahtinen et al 1 evaluating faecal microbiota transplantation (FMT) in IBS; Forty-nine IBS patients were randomised to receive either autologous stool or al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…for improving the outcome of FMT in IBS. 2,3 These included the donor, the dose of the faecal transplant, the route of FMT administration and the issue of single or repeated transplantation.…”
Section: The Study Of Lahtinen Et Al Has Been Commented Upon By Segalmentioning
confidence: 99%
See 2 more Smart Citations
“…for improving the outcome of FMT in IBS. 2,3 These included the donor, the dose of the faecal transplant, the route of FMT administration and the issue of single or repeated transplantation.…”
Section: The Study Of Lahtinen Et Al Has Been Commented Upon By Segalmentioning
confidence: 99%
“…This article is linked to Lahtinen et al papers. To view these articles, visit https://doi.org/10.1111/apt.15942 and https://doi.org/10.1111/ apt.16122 Magdy El-Salhy 1, 2,3 Trygve Hausken 2,3 Jan Gunnar Hatlebakk 2,3 1. Lahtinen P, Jalanka J, Hartikainen A, et al Randomised clinical trial: faecal microbiota transplantation versus autologous placebo administered via colonoscopy in irritable bowel syndrome.…”
Section: N K Ed Co Ntentmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank El-Salhy et al their interest in our study 1,2 and for contributing to the active discussion on how to improve the designs of future faecal microbiota transplantation (FMT) studies. [3][4][5][6] We showed a mild transient benefit of FMT administered once via colonoscopy for irritable bowel syndrome (IBS) patients, although the difference was not significant when compared to placebo. 2 Still, FMT for this patient group shows promise, as also shown by the good results achieved in the clinical trial of El-Salhy et al, showing that a single FMT via gastroscopy resulted in a significant symptom reduction three months after treatment.…”
Section: Letter: Faecal Microbiota Transplantation For Irritable Bowementioning
confidence: 99%
“…We thank Dr Segal and colleagues for their interest and insightful comments on our article 1 in which we reported the results of our placebo‐controlled trial in 49 patients with irritable bowel syndrome (IBS) 2 . We showed that the donor microbiota engrafted for the 1‐year follow‐up, but found no uniform and long‐lasting symptom reduction in these patients.…”
mentioning
confidence: 96%